The aquaVIT-1 intercomparison of atmospheric water vapor measurement techniques - Fahey, David W.; Gao, R.-S.; Möhler, O.; Saathoff, Harald; Schiller, C.; Ebert, Volker; Krämer, M.; Peter, T.; Amarouche, N.; Avallone, L. M.; Bauer, R.; Bozóki, Z.; et al. (Atmospheric measurement techniques, 2014)
Abstract. The AquaVIT-1 intercomparison of atmospheric water vapor measurement techniques was conducted at the aerosol and cloud simulation chamber AIDA (Aerosol Interaction and Dynamics in the Atmosphere) at the Karlsruhe Institute of Technology, Germany, in October 2007. The overall objective was to intercompare state-of-the-art and prototype atmospheric hygrometers with each other and with independent humidity standards under controlled conditions. This activity was conducted as a blind intercomparison with coordination by selected referees. The effort was motivated by persistent discrepancies found in atmospheric measurements involving multiple instruments operating on research aircraft and balloon platforms, particularly in the upper troposphere and lower stratosphere, where water vapor reaches its lowest atmospheric values (less than 10 ppm). With the AIDA chamber volume of 84 m3, multiple instruments analyzed air with a common water vapor mixing ratio, by extracting air into instrument flow systems, by locating instruments inside the chamber, or by sampling the chamber volume optically. The intercomparison was successfully conducted over 10 days during which pressure, temperature, and mixing ratio were systematically varied (50 to 500 hPa, 185 to 243 K, and 0.3 to 152 ppm). In the absence of an accepted reference instrument, the absolute accuracy of the instruments was not established. To evaluate the intercomparison, the reference value was taken to be the ensemble mean of a core subset of the measurements. For these core instruments, the agreement between 10 and 150 ppm of water vapor is considered good with variation about the reference value of about ±10% (±1σ). In the region of most interest between 1 and 10 ppm, the core subset agreement is fair with variation about the reference value of ±20% (±1σ). The upper limit of precision was also derived for each instrument from the reported data. The implication for atmospheric measurements is that the substantially larger differences observed during in-flight intercomparisons stem from other factors associated with the moving platforms or the non-laboratory environment. The success of AquaVIT-1 provides a template for future intercomparison efforts with water vapor or other species that are focused on improving the analytical quality of atmospheric measurements on moving platforms.